Management and Shocks to Worker Productivity - Adhvaryu, Achyuta; Kala, Namrata; Nyshadham, Anant (Journal of Political Economy, 2022)
We study how managers mitigate the negative impacts of environmental shocks. Pairing productivity data from a garment firm with granular measures of air pollution, we show that productivity suffers as a result of pollution shocks but that managers respond by reallocating particularly sensitive workers to improve worker-to-task matches, thus mitigating team productivity losses. Responses are smaller for more inattentive managers; these same managers are also least able to mitigate productivity declines. These patterns are confirmed by leveraging variation in opportunities for reallocation and comparing how close managers of differing attentiveness can get to the simulated production frontier by reallocating workers.